Viroinformatics investigation of B-cell epitope conserved region in SARS-CoV-2 lineage B.1.1.7 isolates originated from Indonesia to develop vaccine candidate against COVID-19 - Arif N. M. Ansori; Reviany V. Nidom; Muhammad K. J. Kusala; Setyarina Indrasari; Irine Normalina; Astria N. Nidom; Balqis Afifah; Kartika B. Sari; Nor L. Ramadhaniyah; Mohammad Y. Alamudi; Umi Cahyaningsih; Kuncoro P. Santoso; et al. (GarVal Editorial Ltda., 2021)
Context: SARS-CoV-2, a member of family Coronaviridae and the causative agent of COVID-19, is a virus which is transmitted to human and other mammals. Aims: To analyze the B-cell epitope conserved region and viroinformatics-based study of the SARS-CoV-2 lineage from Indonesian B.1.1.7 isolates to invent a vaccine nominee for overcoming COVID-19. Methods: The sequences of seven Indonesian B.1.1.7 isolates, Wuhan-Hu-1 isolate, and WIV04 isolate were extracted from the GISAID EpiCoV and GenBank, NCBI. MEGA X was employed to understand the transformations of amino acid in the S protein and to develop a molecular phylogenetic tree. The IEDB was implemented to reveal the linear B-cell epitopes. In addition, PEP-FOLD3 web server was utilized to perform peptide modeling, while docking was performed using PatchDock, FireDock, and the PyMOL software. Moreover, in silico cloning was developed by using SnapGene v.3.2.1 software. Results: In this study, the changes of amino acid in all seven Indonesian B.1.1.7 isolates were uncovered. Furthermore, various peptides based on the B-cell epitope prediction, allergenicity prediction, toxicity prediction from S protein to generate a vaccine contrary to SARS-CoV-2 were identified. Furthermore, the development of in silico cloning using pET plasmid was successfully achieved. Conclusions: This study exhibits the transformations of amino acid in Indonesian B.1.1.7 isolates, and proposes four peptides ("LTPGDSSSGWTAG", "VRQIAPGQTGKIAD", "ILPDPSKPSKRS", and "KNHTSPDVDLG") from S protein as the candidate for a peptide-based vaccine. However, further advance trials such as in vitro and in vivo testing are involved for validation.